The priests in the prophets the portrayal of priests, prophets, and other religious specialists in the latter prophets - Grabbe, Lester L.; Bellis, Alice Ogden, 1950- (London ; New York : T & T Clark International, 2004)
Since at least the 19th century Hebrew Bible scholarship has traditionally seen priests and prophets as natural opponents, with different social spheres and worldviews. In recent years several studies have started to question this perspective. The Priests in the Prophets examines how the priests are portrayed in the Latter Prophets and analyzes the relationship between priests and prophets. The contributors also provide insights into the place of priests, prophets, and some other religious specialists in Israelite and Judean society in pre-exilic and post-exilic times.
Priestly purity and prophetic lunacy: Hosea 1.2-3 and 9.7 / Richard D. Nelson -- What was the image of jealousy in Ezekiel 8? / Margaret S. Odell -- Layers of meaning: priesthood in Jeremiah MT / Corrine Patton -- The priests in the book of Malachi and their opponents / Joachim Schaper -- The prophet versus priest antagonism hypothesis: its history and origin / Ziony Zevit.
Includes bibliographical references and indexes.
Description based on print version record.
Keywords: Bible. -- Criticism, interpretation, etc; Priests; Prophets; RELIGION -- Biblical Studies -- Prophets; Profeten; Priesters; Profeten (bijbelboeken); Electronic books